The Effect of storage and type of Containers used for Transporting Olive Fruits on the Characteristics of the Resulting Olive Oil - شحيده راحيل (Submission and Review of Research -Biological Sciences Series, 2025)
This study investigated the impact of olive fruit storage on the quality of the resulting olive oil. Initially, the fruits were harvested and immediately processed using a hydraulic press without any prior storage; this treatment was considered the control (A). Subsequently, the fruits were stored for five days in plastic crates before processing, forming treatment (B). In treatment (C), the fruits were also stored for five days, but in jute sacks prior to oil extraction The results revealed that storing olive fruits before pressing—whether in terms of duration or storage method—had a clear and direct influence on the chemical and physical properties of the resulting oil, particularly regarding oxidative indicators and antioxidant compounds. Ultraviolet absorbance at 232 nm and 270 nm, along with peroxide value, increased in treatments B and C compared to the control (A), though the values remained within acceptable health limits. A notable decrease in polyphenol, carotenoid, and chlorophyll contents was observed in treatments B and C, with the greatest decline recorded in treatment C. Carotenoids exhibited the highest sensitivity to increased temperature, with a reduction rate of 20.1%, followed by chlorophyll (14.55%), and total phenols (7.5%).